Expanding Housing Finance to the Underserved in South Asia : Market Review and Forward Agenda. - Nenova, Tatiana (Online access: World Bank World Bank Open Knowledge Repository., 2010)
Rapid economic growth in South Asia, urbanization, and a rising middle class have created considerable pent-up demand for housing and housing finance. More than 14 percent of low-income South Asians have no home. In response, South Asia?s dynamic housing and housing finance markets have grown at rates of around 30%, but are still limited to upper-income groups. The contribution of housing and real-estate sector to overall economic growth, social uplift and employment is considerable. Housing and housing finance services have the clear potential to expand to middle- and even lower- income famil.